PENGARUH UNGGAHAN INSTAGRAM @NADYALUQYANA SEBAGAI PENGGUJNA VAPE TERHADAP SIKAP FOLLOWERS (Universitas Negeri Surabaya, 2022)
Information and technology will continue to develop, social media is a given means of advances in technology and information. Social media is in great demand by various groups, social media that is popular and in great demand by the audience is Instagram. In Instagram, there are many Influencers who are someone who has an influence on their followers, one of which is Nadya Luqyana. Nadya is a woman uses a vape, in her content she often uses a vape in her uploads. The S-O-R (Stimulus – Organism – Response) theory is the theory used in this study, which is to find out how Nadya's Instagram followers behave towards her uploads, and also with the help of two theories to assist this research, namely media exposure theory and attitude theory. The approach used in this research is quantitative and uses the method of distributing surveys or questionnaires or questionnaires. The sampling technique used is random sampling because the sample will be taken at random, so each respondent in the population will have the same opportunity to be selected as a sample. The number of followers that will be used as research is 100 people and distributed using a questionnaire link via Google Form and how to calculate the score assisted by a Likert scale. The results of the data from filling out the questionnaire were processed using Product Moment correlation, Cronbach's Alpha, and Spearman Rank correlation. In the hypothesis test it produces a significance value of 0.000 and the value is smaller than 0.050 , then Ho is rejected and Ha is accepted, that is, there is a positive and significant influence of the Instagram Upload variable on the Follower Attitude variable and the correlation value is 0.461 which is on a scale between 0 .40 – 0.599, so it can be explained that the influence is quite strong and significant between the two variables.